"He should so be in jail": An Empirical Study on Preverbal So in American English. (March 2021) - Stange, Ulrike
This paper explores the use of so-called GenX so as a modifier of verb phrases, as exemplified in "He should so be in jail" (SOAP, DAYS, 2005). Drawing on over 1350 relevant tokens retrieved from the Corpus of American Soap Operas (SOAP) (Davies 2011-, 100 million words from 2001-2012), the main purpose of the present study is to provide robust empirical evidence for various findings yielded by small-scale studies and by introspection. The results corroborate some of the previous findings, while others, particularly those based on introspection, are challenged in light of empirical (counter)evidence. The data show that preverbal so is very flexible in that it can occur in various syntactic slots and with a large number of different verbs (wide collocational range) and with different kinds of verbs (full, modal, auxiliary). In a large data set (such as that from SOAP), GenX so is even attested in questions, before auxiliaries in affirmative uses, and after the negator not . Moreover, preverbal so is expanding its functional range from intensification to emphasis.